Investigation of a synonymous mutation in Btk in a patient with agammaglobulinemia: A case report - Cindy Srinivasan; Afshin Shameli; Bruce Ritchie; Adil Adatia (Immunity, Inflammation and Disease, 2023)
Abstract Background X‐linked agammaglobulinemia (XLA) is the most common form of agammaglobulinemia and is caused by mutations in Btk, which encodes Bruton tyrosine kinase (BTK). Case Description We describe a 36‐year‐old male who presented as an infant with hypogammaglobulinemia and sinopulmonary infections and was initially diagnosed with common variable immunodeficiency. Genetic testing showed he was hemizygous for Btk c.240G > A. This synonymous variant affecting the last nucleotide of exon 3 leads to aberrant splicing of most but not all mRNA transcripts. Conclusion We demonstrated reduced BTK protein expression confirming the pathogenicity of the variant and related our findings to genotype‐phenotype relationship studies ina XLA caused by synonymous mutations.